Features of the Kassite’s period in ancient Iraq (1595 BC -1157 BC) - el aidani, samir (Journal of Social Sciences and Humanities, 2021)
Babylonian political and military history includes the various dynasties that passed through the rule of the city of Babylon, and includes, according to the lists of Babylonian kings, eleven dynasties, starting with the "First Babylonian dynasty", known as the Old Babylonian Dynasty or the "Hammurabi Dynasty", and then the "Second Babylonian Dynasty". Known as the "Kingdom of the Land of the Sea" and the "Third Babylonian Dynasty", known as the "Kashi Dynasty", and to the "Babylonian 11th Dynasty", known as the "Chaldean State", (626 B.C./ 539 B.C.), i will focus on the Babylonian dynasty. The third known as the "Kashia" dynasty, which is considered the longest-reigning Babylonian dynasty but the most mysterious in historical studies.